2011
DOI: 10.1007/s00441-011-1173-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and cytoarchitectural remodeling during spinal cord reconnection in the fresh-water turtle Trachemys dorbignyi

Abstract: In fresh-water turtles, the bridge connecting the proximal and caudal stumps of transected spinal cords consists of regenerating axons running through a glial cellular matrix. To understand the process leading to the generation of the scaffold bridging the lesion, we analyzed the mitotic activity triggered by spinal injury in animals maintained alive for 20–30 days after spinal cord transection. Flow cytometry and bromodeoxyuridine (BrdU)-labeling experiments revealed a significant increment of cycling cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…During embryonic development the transient expression of BLBP parallels neurogenesis, and there is evidence from transgenic mouse studies that nearly all neurons in the mouse brain are derived from BLBP + RG [53]. Additionally, BLBP + cells with RG morphology are localized to the central gelatinosa surrounding the central canal in the adult turtle [72, 75], are implicated in the reconnection of the turtle spinal cord after transection [68, 76] and are directly involved in the regeneration of the axolotl spinal cord after amputation of the tail [77]. In mammalian models of injury, BLBP + cells do not reconnect the spinal cord but undergo mitosis at an increased rate after injury [52].…”
Section: Proliferation In the Intact Spinal Cordmentioning
confidence: 99%
“…During embryonic development the transient expression of BLBP parallels neurogenesis, and there is evidence from transgenic mouse studies that nearly all neurons in the mouse brain are derived from BLBP + RG [53]. Additionally, BLBP + cells with RG morphology are localized to the central gelatinosa surrounding the central canal in the adult turtle [72, 75], are implicated in the reconnection of the turtle spinal cord after transection [68, 76] and are directly involved in the regeneration of the axolotl spinal cord after amputation of the tail [77]. In mammalian models of injury, BLBP + cells do not reconnect the spinal cord but undergo mitosis at an increased rate after injury [52].…”
Section: Proliferation In the Intact Spinal Cordmentioning
confidence: 99%
“…By the end of embryogenesis most mammalian radial glia differentiate as astrocytes (Rakic, 2003). However in anamniotes radial glia persist widely in the CNS (García-Verdugo et al, 2002; Naujoks-Manteuffel and Roth, 1989; Zupanc and Clint, 2003), and their continued presence has been implicated in the striking ability of these animals to regenerate following injury (Chernoff et al, 2003; Hui et al, 2010; Rehermann et al, 2011). Thus radial glia have been suggested to represent an endogenous neural stem cell population.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies have also demonstrated axon regeneration after complete spinal cord transection in the turtle (Garcia et al, 2012; Rehermann et al, 2009; Rehermann et al, 2011). After injury, axon regeneration, primarily of propriospinal and sensory neurons, is followed by partial restoration of locomotion in ~50% of spinalized turtles (Rehermann et al, 2009; Rehermann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…After injury, axon regeneration, primarily of propriospinal and sensory neurons, is followed by partial restoration of locomotion in ~50% of spinalized turtles (Rehermann et al, 2009; Rehermann et al, 2011). In this model, histological assays demonstrated that a blood clot filled with red and white blood cells formed immediately after SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation